2013
DOI: 10.1093/bja/aes400
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine as an adjuvant to ropivacaine prolongs peripheral nerve block: a volunteer study

Abstract: A profound prolongation of UNB of ∼60% was detected with perineural dexmedetomidine when added to 0.75% ropivacaine. The systemic administration of 20 µg dexmedetomidine resulted in a prolongation of ∼10% during UNB with 0.75% ropivacaine. Eudra-CT No.: 2012-000030-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
220
3
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(250 citation statements)
references
References 15 publications
23
220
3
4
Order By: Relevance
“…The difference was not found to be statistically significant. Similar findings were found in the studies conducted by Zhang Y and Marhofer et al [11,12] . Moreover they also found that the duration of sensory and motor blockade was more when Dexmedetomidine was used than in patients in whom only ropivacaine was used [13] .…”
Section: Discussionsupporting
confidence: 92%
“…The difference was not found to be statistically significant. Similar findings were found in the studies conducted by Zhang Y and Marhofer et al [11,12] . Moreover they also found that the duration of sensory and motor blockade was more when Dexmedetomidine was used than in patients in whom only ropivacaine was used [13] .…”
Section: Discussionsupporting
confidence: 92%
“…(16,18,23) Marhofer et al reported a profound prolongation of ulnar nerve block (UNB) of 60% with perineural dexmedetomidine when added to 0.75% ropivacaine whereas, systemic administration of 20 mcg dexmedetomidine resulted in a prolongation of only 10% during UNB with 0.75% ropivacaine. (24) It is unlikely that perineural administration of drug would produce significant systemic side effects, but a central effect that results from the systemic absorption of the drug cannot be excluded.…”
Section: Diagram 2: Trend In Mean Arterial Pressurementioning
confidence: 99%
“…The prospective, double-blinded, controlled volunteer study conducted by Marhofer et al using dexmedetomidine (20µg) as additive with (0.75%) ropivacaine in ultrasound guided ulnar nerve block revealed, 60% prolongation of sensory and motor block with perineural dexmedetomidine . 7 Kathuria et al in their study obtained similar results with 50µg dexmedetomidine in 30ml of 0.5% ropivacaine for SBPB. 8 Swami et al concluded that dexmedetomidine (1μg/kg) when added to local anaesthetic (bupivacaine 0.25%) in SBPB increased the duration of sensory and motor block and also the duration of analgesia.…”
Section: Discussionmentioning
confidence: 52%
“…Similar results were also obtained by Marhofer et al with perineural dexmedetomidine and Kaygusuzet al with dexmedetomidine in axillary brachial plexus block. 7,14 However Das et al noticed that when dexmedetomidine was added to 0.5% ropivacaine in supraclavicular brachial plexus block, there was no clinically significant difference in the onset of block. 15 Similarly Rancourt et al evaluated the effect of dexmedetomidine (1μg/kg) when added to 10ml of 0.5% ropivacaine for posterior tibial nerve block.…”
Section: Discussionmentioning
confidence: 99%